2015
DOI: 10.1002/lary.25336
|View full text |Cite
|
Sign up to set email alerts
|

Use of continuous positive airway pressure after rhinoplasty, septoplasty, and sinus surgery: A survey of current practice patterns

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…In a recent survey, 407 rhinoplasty surgeons reported that many of them temporarily suspend CPAP after nasal surgery, typically for a period of 1 to 2 weeks. 33 In the same study, many surgeons reported suspending CPAP postoperatively with minimal complications. The lack of uniformity on OSA screening preoperatively and reintroduction of postoperative CPAP poses a potential health burden on the patient.…”
Section: Osa and Rhinoplastymentioning
confidence: 95%
“…In a recent survey, 407 rhinoplasty surgeons reported that many of them temporarily suspend CPAP after nasal surgery, typically for a period of 1 to 2 weeks. 33 In the same study, many surgeons reported suspending CPAP postoperatively with minimal complications. The lack of uniformity on OSA screening preoperatively and reintroduction of postoperative CPAP poses a potential health burden on the patient.…”
Section: Osa and Rhinoplastymentioning
confidence: 95%
“…2-9 Otolaryngologists frequently encounter scenarios where PAP therapy is purposely withheld postoperatively, such as endoscopic sinus surgery, where there is currently no consensus on the use of postoperative PAP. 10…”
mentioning
confidence: 99%
“…Length of activity and CPAP restrictions must balance possible economic and physiologic consequences to patients with the potential for increased risk of postoperative CSF leak. To date, there are no studies assessing effects of postoperative restrictions on CSF leak rates, and only 1 study exploring practice patterns in the use of CPAP after nasal surgery that did not assess CSF leak rates . Thus, postoperative restrictions are an important area of potential future study.…”
Section: Discussionmentioning
confidence: 99%